AGRONOMIC PERFORMANCE OF SESAME (Sesamum indicum) UNDER DIFFERENT FERTILIZER MANAGEMENT - Dollison, Mohammad D.; Dollison, Beverly Branzuela (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
The sesame crop is one of the earliest crops that is being grown for edible oil purposes. The production performance of this crop is often affected by different factors such as soil fertility, water, and climatic conditions. This study evaluated the performance of sesame under different fertilizer management like animal manure, guano, vermicast, inorganic fertilizer, and no fertilizer application as check plots. The study showed that applying guano fertilizer significantly improved plant height performance 30 to 60 days after planting compared to inorganic fertilizer, other organic fertilizers, and treatments without fertilizer application. The number of capsules per plant produced by sesame was significantly higher with guano fertilizer application compared to treatments without fertilizer application and other organic and inorganic fertilizer sources as treatments. Similarly, the yield performance of sesame under different fertilizer applications resulted in a significant performance over guano fertilizer, with the highest yield obtained compared to other fertilizer management. The different organic and inorganic fertilizers are good sources of essential nutrients for sesame production. Likewise, further study can be conducted using a fertilizer combination, both organic and inorganic, for a better fertilizer management recommendation.